Pemanfaatan Media Berbasis Virtual Reality (VR) untuk Meningkatkan Kognitif Anak Berkebutuhan Khusus - Nurgalbi, Nurgalbi; Purmadi, Ary (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Children with Special Needs (ABK) are children who have uniqueness and various limitations, in the learning process also have different ways or methods from children in general. Therefore, the use of media in learning Children with Special Needs (ABK) is very important, of course it must be in line with the needs or potential mastered by each child. An effective educational technique for children with special needs is by implementing visual-based educational media. By utilizing visual-based educational media, children with special needs are more enthusiastic and better understand the material presented in learning, an example of the use of visual media in learning is implementing Virtual Reality (VR)-based media. The purpose of this study is to utilize Virtual Reality (VR)-based media to improve the cognitive abilities of Children with Special Needs using the Systematic Literature Review (SLR) method. Data accumulation is carried out in a structured manner by recording all articles related to this study, a total of 29 journal articles were found. Based on the results of this study, it states that the utilization and use of VR-based media can improve the cognitive aspects of Children with Special Needs, such as memory, understanding concepts, and active involvement in the learning process. Therefore, VR media has the potential to be a strategic alternative in inclusive education that is oriented to the individual needs of students.